Efficient green light-excited switches based on dithienylethenes with BF2-doped π-conjugated systems. Issue 89 (23rd October 2019) - Li, Ziyong; Dai, Yijie; Lu, Zhiqiang; Pei, Yingying; Chen, Hong; Zhang, Lilei; Duan, Ying; Guo, Hui
Abstract : Novel dithienylethene derivatives with BF2 -doped π-conjugation show efficient green light-excited photoswitching behaviors in solvents, PMMA film and living cells. Abstract : A series of dithienylethenes 1a–1d with BF2 -doped π-conjugation have been successfully developed. Upon alternating irradiation with green light and red/NIR light, they show efficient photochromism and fluorescence switching behaviors in toluene and PMMA film. Moreover, the fluorescence of 1a can be switched effectively in living cells.